Phenotypic and molecular consequences of overexpression of metal-homeostasis genes - Antosiewicz, Danuta Maria; Barabasz, Anna; Siemianowski, Oskar (Frontiers in Plant Science, 2014)
Metal hyperaccumulating plants are able to store very large amounts of metals in their shoots. There are a number of reasons why it is important to be able to introduce metal hyperaccumulation traits into nonaccumulating species (e.g., phytoremediation or biofortification in minerals) and to engineer a desired level of accumulation and distribution of metals. Metal homeostasis genes have therefore been used for these purposes. Engineered accumulation levels, however, have often been far from expected, and transgenic plants frequently display phenotypic features not related to the physiological function of the introduced gene. In this review, we focus on an aspect often neglected in research on plants expressing metal homeostasis genes: the specific regulation of endogenous metal homeostasis genes of the host plant in response to the transgene-induced imbalance of the metal status. These modifications constitute one of the major mechanisms involved in the generation of the plant’s phenotype, including unexpected characteristics. Interestingly, activation of so-called “metal cross-homeostasis” has emerged as a factor of primary importance.